Measuring the concentration of military power in the international geopolitical system: Singer’s methodology using only military indicators - Bunyavejchewin, Poowin; Thavornyutikarn, Supruet; Faugchun, Pattanarat; Kamonpetch, Porntep (Frontiers in Political Science, 2024)
This study quantitatively examines the impact of the COVID-19 pandemic on the concentration of military power within the international geopolitical system from 2014 to 2023. Utilizing a modified Composite Indicator of National Capability (mCINC) based on defense budgets and military personnel, this study analyzes the relative concentration of military capabilities among 145 states. Derived from the Correlates of War Project, our methodology enables an examination of variations in military capability concentration, especially during the pandemic years. The results trend towards the dispersion of military capabilities, with notable variations observed during the COVID-19 period, reflecting a more equitable distribution among states, notably major powers. These variations are attributed to a decrease in military capabilities among democracies, particularly the United States, and an increase in Russia’s military power. The study concludes that the pandemic years have led to a nuanced adjustment towards greater multipolarity, hinting at potential instability and uncertainty in geopolitics.